2009
DOI: 10.1080/10409280802581276
|View full text |Cite
|
Sign up to set email alerts
|

Parent Reading Belief Inventory: Reliability and Validity With a Sample of Mexican American Mothers

Abstract: Research Findings The purpose of the current study was to (a) evaluate the internal consistency of the 7 scales of the Parent Reading Belief Inventory (PRBI), (b) assess the factor structure, and (c) examine concurrent validity in a sample of Mexican American mothers from low-income homes. Two hundred and seventy-four mothers of preschool children completed the PRBI and the Home Literacy Activities Questionnaire. Five of the seven scales demonstrated adequate internal consistency. Principal component and paral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 42 publications
0
20
0
1
Order By: Relevance
“…Literacy beliefs mediate the relationship between parent characteristics (e.g., maternal education) and a host of child outcomes, including vocabulary development (Rogoff, Moore, Correa-Chávez, & Dexter, 2015), and are essential in understanding the connection between a child-rearing environment and culture (Rodríguez, Hammer, & Lawrence, 2009). Beliefs are actualized in the resource (e.g., books) provisions parents make, the structure of the home environment, and everyday routines and activities with children (DeBaryshe, Binder, & Buell, 2000;Sigel & McGillicuddy-De Lisi, 2002;Weigel et al, 2006).…”
Section: Parental Literacy Beliefsmentioning
confidence: 98%
“…Literacy beliefs mediate the relationship between parent characteristics (e.g., maternal education) and a host of child outcomes, including vocabulary development (Rogoff, Moore, Correa-Chávez, & Dexter, 2015), and are essential in understanding the connection between a child-rearing environment and culture (Rodríguez, Hammer, & Lawrence, 2009). Beliefs are actualized in the resource (e.g., books) provisions parents make, the structure of the home environment, and everyday routines and activities with children (DeBaryshe, Binder, & Buell, 2000;Sigel & McGillicuddy-De Lisi, 2002;Weigel et al, 2006).…”
Section: Parental Literacy Beliefsmentioning
confidence: 98%
“…Also low and unsatisfactory internal consistency values in this subscale as well as in other surveys carried out in other countries. More specifically in Mexico Rodriguez et al (2009) found low reliability on Environmental Input and Reading Instruction subscales, in Albania, Dhima (2015) on subscales of Environmental Input, Reading Instruction and in Serbia, Radisic and Seva (2013), on Environmental Input, Resources, Teaching Efficacy subscales.…”
Section: Internal Consistencymentioning
confidence: 99%
“…Alpha coefficients were adequate ranging from .63 to .90. Finally, structure of a factor was revealed by the Rodriguez et al (2009) analysis. These researchers investigated the Mexican-American parents' beliefs using PRBI coupled with Home Literacy Activities Questionnaire.…”
Section: Previous Research Approaches About the Adaption Of Prbimentioning
confidence: 99%
“…The nine items are rated on a 4-point Likert scale, ranging from 1 = Strongly Disagree, 2 = Disagree, 3 = Agree, to 4 = Strongly Agree. Sample items are "Reading helps children be better talkers and better listeners; I ask my child a lot of questions when we read; I find it boring or difficult to read to my child (reverse coded)" Higher PRBI scores reflect endorsement of US school's literacy beliefs, and research has shown that Mexican-American women who hold beliefs consistent with the schools' literacy beliefs engage more frequently in literacy practices [28,29].…”
Section: Verbal Participationmentioning
confidence: 99%
“…The full PRBI scale was developed to examine parents' beliefs about goals and process of reading aloud to young children and theories of emergent literacy and environmental influence on language development. This scale has been previously validated in Mexican-American parents who averaged 11.12 (SD = 1.62) years of formal education [29]. The verbal participation subscale assesses the value placed on children's active verbal participation when reading.…”
Section: Verbal Participationmentioning
confidence: 99%